2021
DOI: 10.1093/bjs/znaa171
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous tibial nerve stimulation in patients with severe low anterior resection syndrome: randomized clinical trial

Abstract: Background Treatment of low anterior resection syndrome (LARS) is challenging. Percutaneous tibial nerve stimulation (PTNS) can improve select bowel disorders. An RCT was conducted to assess the efficacy of PTNS compared with sham stimulation in patients with severe LARS. Method This was a multicentre, double-blind RCT. Patients with major LARS score were allocated to receive PTNS or sham therapy (needle placement simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…With regard to the outcome measures, the LARS score [ 21 ] was adopted to assess the bowel function after anterior rectal resection for colorectal cancer in all the included studies. Additionally, to assess the frequency, type, and severity of fecal incontinence, the obstructed defecation syndrome (ODS) score [ 22 ] was employed in three studies [ 17 , 19 , 20 ], the St. Mark Fecal Incontinence score [ 23 ] was used in two studies [ 18 , 20 ], and the Wexner score [ 24 ] and the Fecal Incontinence Severity Index (FISI) [ 25 ] were adopted in one study each [ 16 , 19 ]. The impact of fecal incontinence on the patient quality of life was evaluated using the Fecal Incontinence Quality of Life (FIQL) score in three studies [ 16 , 19 , 20 ] and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire [ 26 ] in three other studies [ 17 - 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…With regard to the outcome measures, the LARS score [ 21 ] was adopted to assess the bowel function after anterior rectal resection for colorectal cancer in all the included studies. Additionally, to assess the frequency, type, and severity of fecal incontinence, the obstructed defecation syndrome (ODS) score [ 22 ] was employed in three studies [ 17 , 19 , 20 ], the St. Mark Fecal Incontinence score [ 23 ] was used in two studies [ 18 , 20 ], and the Wexner score [ 24 ] and the Fecal Incontinence Severity Index (FISI) [ 25 ] were adopted in one study each [ 16 , 19 ]. The impact of fecal incontinence on the patient quality of life was evaluated using the Fecal Incontinence Quality of Life (FIQL) score in three studies [ 16 , 19 , 20 ] and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire [ 26 ] in three other studies [ 17 - 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Enriquez-Navascues et al [17] reported that although LARS scores significantly decreased in both the intervention and control groups, the number of patients transferred from the "major LARS" category to the "no LARS" category was higher in the control group (eight out of 10 patients) than in the intervention group (three out of 13 patients). In two other studies [18,19], the LARS score…”
Section: Rctsmentioning
confidence: 96%
See 3 more Smart Citations